The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1037/h0048589
|View full text |Cite
|
Sign up to set email alerts
|

Spoken and written expression: An experimental analysis.

Abstract: experiments were designed to test for differences between spoken and written expression. These 2 modes were controlled by limiting time for preparation, time for exposition, and by limiting the Ss to 2 balanced topics. Since each S spoke and wrote on the 2 topics each was his own control. Spoken expression produces more material (words, phrases, sentences), more ideas and subordinate ideas, more ancillary ideas, communicative signals, and orientation signals. Spoken expression is more repetitious and more elab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 4 publications
(3 reference statements)
3
41
1
Order By: Relevance
“…Rather than saying whatever comes to mind, or speaking off the cuff, people can take the time to formulate what to say or edit their communication until it is polished (Chafe and Danielewicz 1987;Redeker 1984;Walther 2007Walther , 2011. Horowitz and Newman (1964), for example, found that written communication generated less repetition (of words, as measured by type-token ratio, as well as phrases and whole parts of sentences), more ideas per word, and fewer peripheral or irrelevant ideas (also see Horowitz and Berkowitz 1967). Rettie (2009Rettie ( , 1143 examined text messages and argued that "its asynchrony provides thinking time, enabling interactants to choose their words carefully rather than responding impetuously."…”
Section: The Current Researchmentioning
confidence: 97%
“…Rather than saying whatever comes to mind, or speaking off the cuff, people can take the time to formulate what to say or edit their communication until it is polished (Chafe and Danielewicz 1987;Redeker 1984;Walther 2007Walther , 2011. Horowitz and Newman (1964), for example, found that written communication generated less repetition (of words, as measured by type-token ratio, as well as phrases and whole parts of sentences), more ideas per word, and fewer peripheral or irrelevant ideas (also see Horowitz and Berkowitz 1967). Rettie (2009Rettie ( , 1143 examined text messages and argued that "its asynchrony provides thinking time, enabling interactants to choose their words carefully rather than responding impetuously."…”
Section: The Current Researchmentioning
confidence: 97%
“…Various aspects of difference have been considered: the levels of abstraction in spoken and written language (de Vito, 1967); the frequency with which certain types of linguistic structures appear in oral and written discourse (Blankenship, 1962;Golub, 1969); differing modes of expression at the ideational, structural, and psychological levels (Horowitz and Newman, 1964); and developmental aspects of oral and written language (Harrell, 1957).…”
mentioning
confidence: 99%
“…Subjects in the self-limited condition used only 1/3 as many unique words as did those in the unlimited condition . This is not surprising because the number of unique words, or size of vocabulary , is a function of the total number of words used (Horowitz & Newman , 1964) .…”
Section: Resultsmentioning
confidence: 99%